1999
DOI: 10.1002/(sici)1521-379x(199905)51:5<163::aid-star163>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of Amylose and Amylopectin in Starch Granules Using Enzyme-Gold Labelling

Abstract: Waxy maize (0 % amylose), potato (21 % amylose) and amylomaize (70 % amylose) starches were obtained from Cerestar UK Ltd. 163The independent localisation of amylose and amylopectin in a range of dry and hydrated native starch granules with varying amylose content (0-70 %) has been indirectly visualised using enzyme-gold cytochemical markers. Increasing amylose content was clearly demonstrated to result in distinct changes in granule architecture. In the absence of amylose (waxy maize starch) a framework of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 0 publications
0
16
1
Order By: Relevance
“…Although negative relationships between relative crystallinity and amylose proportion have been proposed (Jenkins and Donald ; Atkin and others ) our results did not follow the same pattern; starch from cultivar Beryl‐R had a relatively low amylose content and low relative crystallinity, whereas starch from Coyne showed relatively high values in both categories (Table and ). Although most cereal (A‐type) and tuber (B‐type) starches follow the conventional theories on the origins of crystallinity and its dependence on amylose/amylopectin proportions (Cheetham and Tao ), C‐type starches, such as Great Northern bean studied here, usually do not follow the same patterns (Hoover and Ratnayake ; Jenkins and Donald ).…”
Section: Resultscontrasting
confidence: 66%
“…Although negative relationships between relative crystallinity and amylose proportion have been proposed (Jenkins and Donald ; Atkin and others ) our results did not follow the same pattern; starch from cultivar Beryl‐R had a relatively low amylose content and low relative crystallinity, whereas starch from Coyne showed relatively high values in both categories (Table and ). Although most cereal (A‐type) and tuber (B‐type) starches follow the conventional theories on the origins of crystallinity and its dependence on amylose/amylopectin proportions (Cheetham and Tao ), C‐type starches, such as Great Northern bean studied here, usually do not follow the same patterns (Hoover and Ratnayake ; Jenkins and Donald ).…”
Section: Resultscontrasting
confidence: 66%
“…Grant et al (2004) also found higher fat content in durum waxy wheat. The influence of amylose on the granule architecture was demonstrated by use of enzyme gold labeling (Atkin et al 1999). In waxy starch, a framework of closely packed concentric layers of amylopectin exists in the granules and is likely to affect the behavior of the endosperm when crushed in the mill.…”
Section: Discussionmentioning
confidence: 99%
“…The independent localization of amylose and amylopectin in starch granules with varying amylose contents (0 -70%) by enzyme-gold labeling (Atkin et al, 1999) revealed that the location of amylose differed with different amylose contents. Amylose in low amylose content potato starch was mainly located in the amorphous growth rings alternating with semi-crystalline growth rings, whereas high amylose content (amylomaize) granules were shown to possess an amylopectin center surrounded by an amylose periphery encapsulated by an amylopectin surface.…”
mentioning
confidence: 99%